Synergizing QCC and PDCA Approaches to Foster Kaizen Practices in Wingbox Production at Karoseri - Sumasto, Fredy; Syaeful, Muhamad Eryl Saputra; Solih, Edwin Sahrial; Suroso, Finna; Paramita, Astriyani Sandya (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
This research applies the Quality Control Circle (QCC) method and the PDCA (Plan-Do-Check-Action) approach to overcome problems in hydraulic cylinder bracket mounts in a manufacturing company. At the